2023
DOI: 10.18502/ijm.v15i1.11923
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the antimicrobial and antivirulence activities of Sidr and Tualang honeys with Manuka honey against Staphylococcus aureus

Abstract: Background and Objectives: Honey is one of the oldest traditional remedies that has been widely utilized to cure a variety of human ailments. The objective of this research was to test and compare the antibacterial activity of Sidr honey (SH) and Tualang honey (TH) to that of Manuka honey (MH) against Staphylococcus aureus. Materials and Methods: The antibacterial activity of MH, SH and TH against S. aureus was investigated by agar well dif- fusion, Minimum Inhibitory Concentration (MIC), Minimum Bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A recent 2023 study used RT-qPCR to evaluate the effect of MH in comparison to other honeys on S. aureus virulence. While all honeys tested in this study showed downregulation of the seven virulence genes investigated ( argF, purC, adh, scdA, pykA, menB and fabG ), MH assays showed the biggest changes (3.2-7.5 fold reduction) ( Al-Kafaween et al., 2023 ). Other studies exploring the effects of MH on staphylococcal virulence found changes in haemolysis and coagulase activity ( Mokhtar et al., 2020 ).…”
Section: Antistaphylococcal Mechanisms Of Mhmentioning
confidence: 69%
See 2 more Smart Citations
“…A recent 2023 study used RT-qPCR to evaluate the effect of MH in comparison to other honeys on S. aureus virulence. While all honeys tested in this study showed downregulation of the seven virulence genes investigated ( argF, purC, adh, scdA, pykA, menB and fabG ), MH assays showed the biggest changes (3.2-7.5 fold reduction) ( Al-Kafaween et al., 2023 ). Other studies exploring the effects of MH on staphylococcal virulence found changes in haemolysis and coagulase activity ( Mokhtar et al., 2020 ).…”
Section: Antistaphylococcal Mechanisms Of Mhmentioning
confidence: 69%
“…In addition, both demonstrated comparable efficacy against the tested Staphylococci, although variations in activity depending on test type (visual versus spectrophotometric analysis) and species were observed ( Tan et al., 2009 ). A different study comparing both MH and TH against S. aureus growth and virulence gene expression found that MH performed significantly better in both parameters than TH ( Al-Kafaween et al., 2023 ).…”
Section: Honey and Its Antibacterial Capacitymentioning
confidence: 99%
See 1 more Smart Citation